Entoloma fissuromarginatum (Entolomataceae, Agaricales), a new species from Battagram District, Pakistan - Khan, Muhammad Binyamin; Sana; Ishaq, Muhammad; Kiran, Munazza; Tarafder, Entaj; Fiaz, Muhammad; Wen, Ting Chi (Phytotaxa, 2026)
A new species, Entoloma fissuromarginatum, is described from the Battagram District, Khyber Pakhtunkhwa Province, Pakistan. The species is delineated based on the combination of morphological characteristics and molecular evidence, with nrITS sequence data supporting its distinct taxonomic status. Entoloma fissuromarginatum is characterized by a hemispherical to plano-concave and light brownish-gray pileus with split margins, adnate and light brownish-gray lamellae, reddish brown and scaly stipe, heterodiametric basidiospores (average 6.40 × 5.61 μm) having 5–6 angles, absence of pleurocystidia, lageniform cheilocystidia, narrowly clavate to subcapitate caulocystidia, and a cutis pileipellis and stipitipellis. A description, phylogenetic analysis results, an illustration, and a comparison with closely related taxa of the new species are provided.